The Integrating Entrepreneurship Education into Islamic Madrasah Curriculum: A Qualitative Case Study of Experiential and Project-Based Learning under Indonesia’s Freedom to Learn (Merdeka Belajar) Initiative - Alvadina, Pani Yuni; Fitrisia, Azmi; Yufriadi, Ferdi; Syahriani, Fadilla; Ngardi, Valensius (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2024)
Purpose – This study aims to develop and evaluate an entrepreneurship-based curriculum aligned with the Freedom to Learn (Merdeka Belajar) initiative at State Madrasah Aliyah in Bukittinggi, Indonesia. Recognizing the necessity of equipping students with entrepreneurial skills, creativity, and self-reliance, this research addresses the critical gap between traditional Islamic education and modern labor market demands Design/methods/approach – A qualitative case-study approach, complemented by quantitative analysis, was utilized. Data collection involved purposive sampling, participatory observation, semi-structured interviews, document analysis, and closed-ended questionnaires. Participants included school leaders, teachers, students, alumni, and parents. Qualitative data were analyzed thematically, while quantitative data provided descriptive statistics to strengthen findings. Findings – The integration of experiential learning and project-based entrepreneurship significantly enhanced students’ practical business skills, creativity, problem-solving ability, and interpersonal competencies. The curriculum explicitly incorporates principles of student autonomy and flexible learning, central to Indonesia’s Freedom to Learn (Merdeka Belajar) initiative. However, substantial challenges were identified, including inadequate infrastructure, limited funding, a shortage of qualified teachers, and societal resistance rooted in traditional perceptions of madrasahs as purely religious institutions. Student questionnaire results indicated positive perceptions of the curriculum’s effectiveness (mean score > 4.2 out of 5). Research implications – Findings provide actionable insights for policymakers, educators, and administrators seeking to implement effective entrepreneurship curricula. Strategic interventions such as enhanced teacher training, structured mentoring, and robust industry collaboration are recommended to address implementation barriers, preparing students for real-world economic challenges and ultimately fostering socio-economic growth and community development.